Intraregional Analysis of the Autoparts and Metalmechanical Sectors of Santander Deparment in the Context of the Pacific Alliance during 2017 and 2021 - Ramírez Montañez, Julio César; Largo, Nicole Juliana; Páez Cubides, Oriana Marcela; Quiroga, María Alejandra (Latin American Journal of Trade Policy, 2022)
The aim of this research was to analyze the intra-regional trade conditions of the auto parts and metal-mechanic sectors of Santander department, during the period 2017-2021. In order to achieve the objective, the intraregional trade indicators were applied to the tariff chapters corresponding to the auto parts and metal-mechanic sectors of Santander. The methodology implemented was based on the application of the indicators granted by the Economic Commission for Latin America and the Caribbean (ECLAC) in order to measure the trade dynamism of a region or a country. Among the main conclusions reached by this research, it is highlighted that the tariff chapter with the highest export dynamics is 84 (Nuclear reactors, boilers, machines, apparatus and mechanical devices) with values ranging between US$ 148,717 and US$ 239,507; the only tariff chapter with high export trend from Santander to the countries of the Pacific Alliance is 73 corresponding to manufactures of iron and steel castings, where the years 2017 and 2019. In imports, tariff chapter 73 stands out, which had the highest dynamism between 2017 and 2021, with imports ranging from $68,954 to $124,118 in the period of analysis. The Intraregional Trade Indicator of imports shows that the department of Santander maintains a low level of imports of auto parts and metal-mechanic products from the Pacific Alliance. The tariff chapters where there is a high import trend are 76 (Aluminum and its manufactures). Regarding the trade balance, the behavior of exports of tariff chapters 82 (Cutlery tools and tools) and 84 (Nuclear reactors, boilers, machines, apparatus and mechanical devices) are highlighted, presenting surplus balances between 2017 and 2021.